2022
DOI: 10.1177/15589250221127393
|View full text |Cite
|
Sign up to set email alerts
|

The impact of sports bra features on measured and perceived pressure for torso movement of the upper body

Abstract: The interpretation of pressure between a sports bra and the skin is highly significant to females, marketers, and designers because it helps reduce discomfort. So far, many studies on sports bras pressure have focused mainly on static activities such as standing or sitting and dynamic activities such as jumping, walking and running, skipping, and jogging that cause vertical movement of the body. Therefore, this study focuses on upper body torsion rather than vertical or horizontal motion. The objective is to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…In a study, encapsulation bras and compression bras were compared according to the compression value they applied to different points of the upper body. According to the results, it was found that encapsulation bras apply less compression than compression bras, and consequently, they were found more comfortable than compression bras (Ocran et al. , 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In a study, encapsulation bras and compression bras were compared according to the compression value they applied to different points of the upper body. According to the results, it was found that encapsulation bras apply less compression than compression bras, and consequently, they were found more comfortable than compression bras (Ocran et al. , 2022).…”
Section: Introductionmentioning
confidence: 99%
“…For example, sports bras are designed to support the soft tissues of the breasts and control breast motion exacerbated during physical activities due to the absence of anatomical support of the breasts [ 3 , 4 ]. However, sports bras which exert high compressive forces on the chest may initiate other physiological and psychological effects on the body such as poor blood flow and wear discomfort [ 5 , 6 ]. Parameters for wear comfort yet have not been verified and pressure evaluations of bras have not been done in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…39 Researchers have also evaluated the physical mechanical and thermal-humid properties of functional sports fabrics, but their applications are limited due to high cost. 40,41 Currently, more female consumers realize the importance of protecting breasts during exercise and put forward higher requirements for bra comfort and functions. 42 It is believed that reasonable style and structure designs of sports bras can improve sports performance, provide comfort, and protect human body from sports-related injuries.…”
mentioning
confidence: 99%